Comportamento ingestivo de cordeiros em terminação a pasto - Von Linsingen Piazzetta, Hugo; Monteiro, Alda Lucia Gomes; Ribeiro, Ticiany Maria Dias [UNESP]; De Faccio Carvalho, Paulo César; Dittrich, João Ricardo; Da Silva, Claudio José Araujo (Universidade Estadual de Maringa, 2009)
The objective of this study was to evaluate intake behavior of lambs in pasture systems: (1) lambs kept with their dams in ryegrass (Lolium multiflorum Lam.) without supplementation; (2) lambs kept with their dams in the same pasture but supplemented in creep feeding; (3) lambs kept with their dams in the same pasture but supplemented in creep grazing with white clover. Three evaluations of intake behavior were performed to check the activities carried out by animals (grazing, rumination, suckling and other activities). Grazing, rumination and other activities times were different (p < 0.05) for non-supplemented lambs. For these lambs, grazing and rumination times were longer than other activities time compared to other systems. Creep feeding reduced grazing time (p < 0.05), probably due to easy access and quality of concentrate. Lambs in creep grazing had reduced (p < 0.05) rumination time. Bite mass in creep grazing was higher (p < 0.05), probably due to easy harvesting of leaves by lambs. It was concluded that the production system affects feeding strategy of lambs and the preference for legumes suggests the use of creep grazing for finishing lambs.
Intake behaviour of lambs finished on pasture
Keywords: Creep feeding; Creep grazing, sheep; Grazing; Ruminating; Suckling; Animalia; Lolium; Lolium multiflorum; Ovis aries; Trifolium repens